Evaluasi Usability Situs Web Snapixa dengan menggunakan Metode Usability Testing dan System Usability Scale - Muhammad Aswin Zulhijdi; Retno Indah Rokhmawati; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Snapixa is an application to make a landing page, owned by Startup Codelaris, which was made in May 2018. This application is still in the pre-release stage, so there are still many usability issues in the application until it is finally released. This study was evaluated to measure the level of usability using the Usability Testing method so as to produce recommendations for improvement by measuring aspects of learnability where the results are 97.65% meaning that the success rate of respondents is good, the aspect of efficiency is 0.0003 goals / sec or the time to complete a task 3 times longer than the expert user, the error aspect of 0.010 means that the respondent's error is relatively small. Satisfaction uses the System Usabilty Scale questionnaire to find out whether the system is suitable for use with 20 active users and the result is 50% -63% meaning it needs to be increased again. Participants tested 8 new users divided into 3 segments, 3 people aged 19-30, 3 people 31-40 and 2 people 41-54 years. Interviews were conducted to explore problems from the application so that they could be evaluated. Based on the results of usability testing and interviews found 9 problems such as user trouble finding the layout of the button elements, the function of the button elements, monochrome colors, input links, save button locations, and changing passwords. From these problems, recommendations for improvement were obtained according to usability guidelines where the results of recommendations for improvement still did not succeed in solving the problem because there was no design and implementation.